The comparison of dairy performance and some reproductive parameters of holstein cows imported from Sweden and their Polish age mates - Ewa Czerniawska-Piątkowska; Maciej Szewczuk; H. Kamieniecki; M. Adamski; A. Bruś; Daniel Falta (Acta Universitatis Agriculturae et Silviculturae Mendelianae Brunensis, 2007)
The general aim of the present work was to compare dairy performance and some reproductive parameters of Holstein-Friesian (HF) cows imported from Sweden as an in-calf heifers, and their age mates in Poland. The animals were kept freely on the deep litter on the farm owned by Agro-company “Witkowo” and feeding was based on TMR (total mixed ration) system during whole year. All ration’s ingredients (bulky feed, concentrate, miscellaneous additives) were mixed and fed as all-mash. The feed ration depended from the physiological condition of a cow and it was composed of corn and grass ensilage, mash concentrate, crushed corn meal, brewer’s grains and beet pulp.Cows imported from Sweden as in-calf heifers obtained higher milk, fat and protein yield in both lactations comparing to home cows. Significant statistical differences were observed for kg of milk, kg of protein, for FCM (P<0.01) and for kg of fat (P<0.05) in 2nd lactation. Fat and protein content in milk was in average higher for home cows (P<0.01). Big differences (P<0.01) were observed in SBT (proportion of protein to fat content) and RTB (difference between concentration of fat and protein) at imported cows in 2nd lactation. As far as reproduction parameters (gestation interval, calving interval, insemination index) are concerned was cows from Sweden better too. Heifers from Sweden calved earlier. The usage of high genetic potential of imported cows is possible only with providing them optimum living conditions suitable to their needs.